Expectations, Taylor Rules and Liquidity Traps - Ji, Yangyang (Journal of Reviews on Global Economics, 2017)
This paper includes three equilibrium paths (Christiano et al. 2011; Werning 2012; Cochrane 2016) that model liquidity traps in a unified framework with expectations of duration of the zero lower bound and expectations of a Taylor-type rule outside of the trap, and finds that their appearance depends on these expectations. Other than that, Werning (2012)'s and Cochrane (2016)'s equilibrium paths require one more strong assumption and are thus arguably harder to observe in reality although Cochrane (2016)'s equilibrium path fits the recent data better.